2010
DOI: 10.1556/abiol.61.2010.suppl.8
|View full text |Cite
|
Sign up to set email alerts
|

The most recent results on orchid mycorrhizal fungi in Hungary

Abstract: Symbionts and endophytes of Hungarian orchids were studied at diverse habitats. Mycobionts of roots and in situ germinated protocorms of 15 orchid species were identified by molecular methods. Four fungal groups could be distinguished from orchids living at diversely wet treeless habitats: Ceratobasidiaceae, Epulorhiza 1, Epulorhiza 2 and Sebacinaceae. While the groups Ceratobasidiaceae and Sebacinaceae were detected only at habitats with medium water supply, members of clade Epulorhiza occurred at all of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…and other members of the Orchidaceae. Studies on French, German and Hungarian C. damasonium plants have revealed that they associate with a variety of basidiomycetes and ascomycetes (Bidartondo et al, 2004;Julou et al, 2005;Illyes et al, 2010). Italian C. longifolia have been shown to associate with Hebeloma, Russula and Tomentella, and Estonian C. longifolia with Thelephoraceae and Sebacina (Abadie et al, 2006;Liebel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…and other members of the Orchidaceae. Studies on French, German and Hungarian C. damasonium plants have revealed that they associate with a variety of basidiomycetes and ascomycetes (Bidartondo et al, 2004;Julou et al, 2005;Illyes et al, 2010). Italian C. longifolia have been shown to associate with Hebeloma, Russula and Tomentella, and Estonian C. longifolia with Thelephoraceae and Sebacina (Abadie et al, 2006;Liebel et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the identification of their mycorrhizal fungi. Fungal diversity in C. damasonium has been assessed in three different works carried out in France, Germany, and Hungary showing that this orchid associates with a variety of both basidiomycetes and ascomycetes (Bidartondo et al, ; Julou et al, ; Illyés et al, ). Abadie et al () and Liebel et al () have respectively reported that C. longifolia associates with several fungal taxa, such as Thelephoraceae and Sebacinaceae in Estonia, whereas Hebeloma , Russula , and Tomentella are the main mycorrhizal fungi in the same orchid species collected in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, very few protocorms were produced by seeds sown in seed packets, and they were almost invariably found in packets placed in the immediate neighbourhood of adult L. lilifolia . Low percentages of seed germination were also reported for L. loeselii at Lake Velence (Hungary), where <5% of the seeds germinated in seed packets placed in the upper 5 cm of floating peat mats (Illyés et al, 2005). The low germination was attributed to the low abundance of appropriate mycorrhizal fungi in floating peat mats.…”
Section: Floral and Seed Charactersmentioning
confidence: 86%
“…All strains supported growth of protocorms in the laboratory. Illyés et al (2005) isolated a similar Tulasnella strain from the roots of adult plants and protocorms of L. loeselii growing on peat mats. Protocorms hosted three additional strains that belonged to the genus Ceratobasidium .…”
Section: Floral and Seed Charactersmentioning
confidence: 99%